Acute effects of different warm-up protocols on junior golfers` drive performance (International Journal of Strength and Conditioning, 2025)
There is a paucity of evidence assessing the efficacy of warm-up interventions with junior golfers. This study assessed the acute effects of warm-up protocols on junior golfers` driving performance. In a randomised, repeated, counter-balanced design, fifteen junior golfers (age=14.77 years ± 2.08; hcp=7.57±6.53) undertook control, dynamic and RAMP (i.e. raise, activate, mobilise, potentiate) warm-up conditions, before club and ball metrics were recorded using a Trackman 4 launch monitor. Repeated measures ANOVAs found significant increases (p<0.05) in club head speed (CHS) (np²=.142), and significant decreases in launch angle (np²=.060), max height (np²=.436) and dispersion (np²=.126) for both conditions compared to control, indicative of a more penetrative ball flight and improved accuracy, however, significant differences between dynamic and RAMP conditions were not observed. Despite increased CHS, golfers were unable to translate this to increased ball speed, thus impacting upon distances achieved. In conclusion, both dynamic and RAMP warm-ups can have acute benefits on measures of golf drive performance in junior golfers. It is recommended that golfers work with Professional Golfers` Association golf coaches and strength and conditioning coaches to assess all impact factor and ball flight metrics when aiming to integrate improvements to on course performance. Future research should also attempt to assess the translation of increased golf driving performance to strokes gained on the golf course with junior golfers.